RESEARCH OF SOCIAL FACTORS OF FORMATION OF THE STUDENT'S LANGUAGE AND COMMUNICATIVE COMPETENCE (BASED ON THE SURVEY OF STUDENTS OF THE FORESTRY SPECIALTIES) - Oksana Hrydzhuk (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2017)
The problem of formation of the student's language and communicative competence in the context of clarification of social factors that affect their learning of the Ukrainian Language for Proficiency is revealed. The results of survey conducted in the Ukrainian National Forestry University in 2013-2016 among the students of the first and second years (the specialities "Forestry and Landscaping" and "The Woodworking Technology") are described. Students' attitude to the Ukrainian language as a means of communication in performing of industrial actions and choosing the language of communication in future professional activities was found out in the analysis. Environmental impact, the factor of a companion, and the peculiarities of speech situation are considered to be among the main social factors that contribute to the student's communication in a certain language. Students' evaluation of their own level of command of the state language as a means of professional communication is defined. Students' understanding of appropriateness of development of language knowledge and also communicative abilities and skills for professional communication are researched. A set of knowledge and skills that students consider as those necessary to be improved is revealed. The appropriateness of studentsʹ language training at high school is outlined. The systems of reasons that are crucial for students during their studies of' the Ukrainian Language for Proficiency are identified. A clear idea of the future profession and understanding what we should know and be able to do, creative development of professional skills and desire to create, increase of social status, and interest in continuing education are highlighted among the values prevailing in attitude to learning in general. Some questions covered the necessity of professional terminology learning in the linguistic aspect. The major reasons that motivate students to learn professional terminology as a separate discipline such as in-depth study of professional terminology, and also formation of the skills of proper use and translation of professional terms are named.